1995
DOI: 10.1016/0735-1097(95)00026-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased echodensity of myocardial wall in the diabetic heart: An ultrasound tissue characterization study

Abstract: Abnormally increased myocardial echodensity, possibly related to collagen deposition, can be detected in asymptomatic diabetic patients with normal rest function. Theoretically, this finding might be considered a very early preclinical alteration potentially related to subsequent development of diabetic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 32 publications
1
49
1
2
Order By: Relevance
“…Furthermore, because cardiac amyloidosis is associated with abnormal echogenicity, we investigated the prognostic value of acoustic quantification with cyclic variation (CV) of integrated backscatter (IB) from the myocardium during the cardiac cycle. 9 -12 Acoustic quantification has been performed with IB ultrasonic imaging under a variety of conditions such as the aging heart, 13 dilated cardiomyopathy, 14,15 hypertrophic cardiomyopathy, 16 -18 myocardial ischemia, 19 -21 diabetes mellitus, 22,23 and cardiac allograft rejection, 24,25 and various abnormalities have been described. We sought to clarify the prognostic value of cycle-dependent variation of myocardial integrated backscatter (CV-IB) analysis in primary (AL) amyloidosis and to compare its prognostic value with that of the previously described 2-dimensional and Doppler flow data.…”
mentioning
confidence: 99%
“…Furthermore, because cardiac amyloidosis is associated with abnormal echogenicity, we investigated the prognostic value of acoustic quantification with cyclic variation (CV) of integrated backscatter (IB) from the myocardium during the cardiac cycle. 9 -12 Acoustic quantification has been performed with IB ultrasonic imaging under a variety of conditions such as the aging heart, 13 dilated cardiomyopathy, 14,15 hypertrophic cardiomyopathy, 16 -18 myocardial ischemia, 19 -21 diabetes mellitus, 22,23 and cardiac allograft rejection, 24,25 and various abnormalities have been described. We sought to clarify the prognostic value of cycle-dependent variation of myocardial integrated backscatter (CV-IB) analysis in primary (AL) amyloidosis and to compare its prognostic value with that of the previously described 2-dimensional and Doppler flow data.…”
mentioning
confidence: 99%
“…Ultrasonic backscatter is a new technique that quantifies fibrosis in myocardium based on collagen content. In a previous study of asymptomatic type I diabetic patients without hypertension or CAD and normal systolic function, septal and posterior wall echodensity was significantly higher in diabetics than controls (42). It was suggested that increased myocardial echodensity is related to augmented collagen deposition and this finding may be early marker for the development of the following DCP (37,42).…”
Section: Diagnosismentioning
confidence: 99%
“…As técnicas são diversas e apresentam variações: a) tipo de correção utilizada -alguns estudos subtraem o valor obtido no tecido sob investigação do observado no referencial 11 , enquanto outros utilizam a divisão entre as duas medidas [12][13][14][15] 11 , embora a utilização de referencial com valores conhecidos de integrated backscatter, também ocorra como phantoms de borracha 10 . No que diz respeito ao tipo de material utilizado como referencial, cabe ressaltar que a medida do integrated backscatter no interior da cavidade ventricular e do pericárdio, não leva em consideração a profundidade da região estudada.…”
Section: O Integrated Backscatterunclassified
“…Esperava-se que o maior acúmulo de colágeno inerente ao processo de fibrose alterasse o coeficiente de backscatter do tecido e, se a téc-nica fosse sensível o suficiente, este aspecto poderia preceder alterações de função ou forma. Essa associação foi demonstrada em modelos que envolveram diversas doenças, como diabetes mellitus 12 , hipertrofia ventricular e miocardiopatia hipertrófica [13][14][15][16]23 , pacientes com talassemia maior em regime de transfusões múltiplas 24 e em alterações cardía-cas decorrentes do uso de quimioterápicos 25 . Em nosso laboratório, documentamos valores de integrated backscatter Fig.…”
Section: O Integrated Backscatterunclassified